mRNA structural elements immediately upstream of the start codon dictate dependence upon eIF4A helicase activity - Waldron, Joseph A. (Genome Biol, 2019)
BACKGROUND: The RNA helicase eIF4A1 is a key component of the translation initiation machinery and is required for the translation of many pro-oncogenic mRNAs. There is increasing interest in targeting eIF4A1 therapeutically in cancer, thus understanding how this protein leads to the selective re-programming of the translational landscape is critical. While it is known that eIF4A1-dependent mRNAs frequently have long GC-rich 5′UTRs, the details of how 5′UTR structure is resculptured by eIF4A1 to enhance the translation of specific mRNAs are unknown. RESULTS: Using Structure-seq2 and polysome profiling, we assess global mRNA structure and translational efficiency in MCF7 cells, with and without eIF4A inhibition with hippuristanol. We find that eIF4A inhibition does not lead to global increases in 5′UTR structure, but rather it leads to 5′UTR remodeling, with localized gains and losses of structure. The degree of these localized structural changes is associated with 5′UTR length, meaning that eIF4A-dependent mRNAs have greater localized gains of structure due to their increased 5′UTR length. However, it is not solely increased localized structure that causes eIF4A-dependency but the position of the structured regions, as these structured elements are located predominantly at the 3′ end of the 5′UTR. CONCLUSIONS: By measuring changes in RNA structure following eIF4A inhibition, we show that eIF4A remodels local 5′UTR structures. The location of these structural elements ultimately determines the dependency on eIF4A, with increased structure just upstream of the CDS being the major limiting factor in translation, which is overcome by eIF4A activity.